Analisis Konstruk Sintaktik Bahasa Jawa Pada Anak Tuna Rungu Wicara (Disphasia) Di Yayasan Rehabilitasi Tuna Rungu Wicara Surakarta - Exwan Andriyan Verrysaputro; Tya Resta Fitriana; Tri Utami (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The aim of this research is to describe the syntactic constructs of the Javanese language for deaf and speech impaired students. This research is included in qualitative research. Data was collected by listening freely and engaging in conversation. After the data is collected, data analysis is carried out. The language analysis technique in this research was carried out using the change of form technique. From the results of data analysis, it can be seen that the syntactic constructs of the Javanese language spoken by deaf and speech impaired children at the Deaf and Speech Impaired Rehabilitation Foundation (YRTRW) are adverbial phrases, single clauses with an active sentence type (ukara Horn) positioned as interrogative sentences ukara pitaken, ukara sambawa, and ukara cariyos.